CORRELATION ECHOMETRIC PARAMETERS OF UTERUS AND OVARIES IN DIFFERENT PHASES OF THE MENSTRUAL CYCLE WITH ANTHROPO-SOMATOTYPOLOGICAL INDICATORS OF HEALTHY GIRLS OF MESOMORPHIC SOMATOTYPE - Tkachenko, M. M.; Cherkasova, L. A. (Journal of Education, Health and Sport, 2015)
Tkachenko М. М., Cherkasova L. A. Кореляції ехометричних параметрів матки та яєчників у різні фази менструального циклу з антропо-соматотипологічними показниками здорових дівчат мезоморфного соматотипу = Correlation echometric parameters of uterus and ovaries in different phases of the menstrual cycle with anthropo-somatotypological indicators of healthy girls of mesomorphic somatotype. Journal of Education, Health and Sport. 2015;5(11):363-372. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34100 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A363-372 https://pbn.nauka.gov.pl/works/671008 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 20.11.2015. УДК 100.42:621.90.02.001.5:612.627:612.621:575.191:613.954 Кореляції ехометричних параметрів матки та яєчників у різні фази менструального циклу з антропо-соматотипологічними показниками здорових дівчат мезоморфного соматотипу CORRELATION ECHOMETRIC PARAMETERS OF UTERUS AND OVARIES IN DIFFERENT PHASES OF THE MENSTRUAL CYCLE WITH ANTHROPO-SOMATOTYPOLOGICAL INDICATORS OF HEALTHY GIRLS OF MESOMORPHIC SOMATOTYPE М. М. Ткаченко, Л. А. Черкасова М. М. Tkachenko, L. A. Cherkasova Національний медичний університет імені О.О. Богомольця, м. Київ National Medical University named after Bohomolets, Kyiv Summary Almost all sonographic uterine size and part of the size ovaries in girls with mesomorphic somatotype identified significant correlations with anthropometric, somatotypological and indicators component composition of body weight during the different phases of the menstrual cycle. All phases of the menstrual cycle inherent uniformity of connections in strength, number and their direction. The length and width of the right ovary, the thickness of the left ovary measured during the follicular phase; the volume of the right and left ovary, width, thickness of the left ovary during ovulation identified; the thickness of the left ovary, determined during the luteal phase, have no statistically significant correlation with any of the indicators of structure and body size. Key words: correlation, uterus, ovaries, sonographic study, girls, body size. Резюме Практично для всіх сонографічних розмірів матки та частини розмірів яєчників у дівчат із мезоморфним соматотипом визначені достовірні кореляції з антропометричними, соматотипологічними і показниками компонентного складу маси тіла в період різних фаз менструального циклу. Всім фазам менструального циклу притаманна однотипність зв’язків за силою, кількістю та їх напрямком. Довжина і ширина правого яєчника, товщина лівого яєчника виміряні під час фолікулінової фази; об’єм правого і лівого яєчника, ширина, товщина лівого яєчника, визначені під час овуляції; товщина лівого яєчника, визначена під час лютеїнової фази, не мають статистично значущих кореляцій з жодним із показників будові і розмірів тіла. Ключові слова: кореляції, матка, яєчники, сонографічне дослідження, дівчата, розміри тіла. Резюме Корреляция ЕХОМЕТРИЧНИХ ПАРАМЕТРОВ МАТКИ И ЯИЧНИКОВ В РАЗНЫЕ ФАЗЫ менструального цикла С антропо-соматотипологическими показателями здоровых ДЕВУШЕК мезоморфного соматотипа. Практически для всех сонографических размеров матки и части размеров яичников у девушек с мезоморфным соматотипом определены достоверные корреляции с антропометрическими, соматотипологическими и показателями компонентного состава массы тела в период различных фаз менструального цикла. Всем фазам менструального цикла присуща однотипность связей по силе, количеству и их направлению. Длина и ширина правого яичника, толщина левого яичника измеренные во время фолликулиновой фазы; объем правого и левого яичника, ширина, толщина левого яичника, определенные во время овуляции; толщина левого яичника, определенная в период лютеиновой фазы, вообще не имеют статистически значимых корреляций с показателями строения и размеров тела. Ключевые слова: корреляции, матка, яичники, сонографическое исследование, девушки, размеры тела.